The null result penalty - Felix Chopra; Ingar Haaland; Christopher Roth; Andreas Stegmann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
In experiments with economists, we measure how the evaluation of research studies depends on whether the study yielded a null result. Studies with null results are perceived to be less publishable, of lower quality, less important, and less precisely estimated than studies with statistically significant results, even when holding constant all other study features, including the precision of estimates. The penalty for null results is of similar magnitude for various subgroups of researchers, from PhD students to editors. The null result penalty is larger when experts predict a non-null result and when statistical uncertainty is communicated in terms of p-values rather than standard errors. Our findings have implications for understanding mechanisms underlying publication bias and the communication of research findings.
Keywords: 330; Null Results; Publication Bias; Learning; Information; Scientific Communication